Carbon nitride composite photocatalyst as well as preparation method and application thereof

By introducing phosphorus and potassium into graphite phase carbon nitride (g-C3N4) photocatalyst for co-doping and introducing co-catalyst CoS to form semiconductor heterojunction, the narrow response range of g-C3N4 photocatalyst in the visible light is solved. The problem of poor carrier transmission capacity significantly improves the photocatalytic performance and reaction rate, and achieves efficient degradation of organic pollutants.

CN119456013AInactive Publication Date: 2025-02-18TIANJIN ACAD OF ECOLOGICAL & ENVIRONMENTAL SCI
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411660847.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-20
Publication Date
2025-02-18
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

The unmodified graphite phase carbon nitride (g-C3N4) photocatalyst has a narrow response range of visible light, poor photogenerated carrier transmission capacity, and easy carrier recombination, resulting in unsatisfactory photocatalytic reaction rate, which limits its development. and application.

Method used

By introducing phosphorus and potassium elements for co-doping, the electronic structure of the catalyst is regulated, the band edge position is changed, the generation ability and light absorption performance of reactive oxygen intermediates are improved, and the co-catalyst CoS is introduced to form a special semiconductor heterojunction to promote photogenesis The diffusion and transmission of electrons improve the separation ability between photogenerated electrons and photogenerated holes.

Benefits of technology

It significantly improves the light absorption performance, conductivity and photocatalytic oxidation capacity of carbon nitride composite photocatalysts, extends the life of photogenerated carriers, and is better than the conventional g-C3N4, phosphorus single-doped g-C3N4 and potassium single-doped Miscellaneous g-C3N4 is also better than phosphorus and potassium co-doped g-C3N4 and CoS-modified g-C3N4, which shows good results in photocatalytic degradation of organic pollutants.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119456013A_ABST
    Figure CN119456013A_ABST
Patent Text Reader

Abstract

The invention belongs to the field of preparation of photocatalysts, and discloses a carbon nitride composite photocatalyst and a preparation method and application thereof.The carbon nitride composite photocatalyst is cobalt sulfide modified phosphorus and potassium co-doped carbon nitride, the carbon nitride is a graphite phase, the doping ratio of P to K to Co to S to S is 1.33-21.7%, g-C3N4 is used as a light absorption active layer, and the carbon nitride composite photocatalyst has the advantages that the light absorption activity of the carbon nitride composite photocatalyst is improved; and phosphorus and potassium elements are co-doped, the electronic structure of the catalyst is regulated and controlled, and the band edge position is changed, so that the generation capability and the light absorption performance of an active oxygen intermediate are improved, the conductivity is improved, meanwhile, a cocatalyst CoS is introduced, and the cocatalyst CoS and the original phosphorus and potassium co-doped catalyst form a special semiconductor heterojunction, so that the photoelectric conversion efficiency is improved. The heterojunction promotes diffusion and transmission of photo-generated electrons and improves the separation capacity of the photo-generated electrons and photo-generated holes, so that the service life of photo-generated carriers is prolonged.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of photocatalyst preparation, and specifically relates to a carbon nitride composite photocatalyst and a preparation method and application thereof. Background Art

[0002] With the acceleration of the industrialization process of human society, environmental pollution problems have become increasingly prominent. Organic pollutants, heavy metal pollutants and various bacteria are increasingly discharged into water bodies, becoming the main source of pollution in water bodies, posing a serious threat to the ecosystem and human health. Among them, organic dye pollution is a widespread source of water pollution, which can still exist stably in water bodies even at very low concentrations. At present, a large amount of research has been conducted on organic matter in wastewater at home and abroad, and a variety of technical methods have been developed to degrade pollutants in water, including biodegradation, membrane filtration, ion exchange, etc., but these water pollution treatment technologies have many problems, such as the process is relatively complicated, requires continuous energy supply, and will cause secondary pollution to the water body.

[0003] Photocatalytic degradation technology has become one of the most cost-effective methods for degrading pollutants due to its safety and sustainability. Generally, photocatalytic technology uses sunlight to irradiate semiconductor catalyst materials to generate photogenerated electrons (e - ) and holes (h + ), and through e - and h + Reacts with H2O or O2 to generate reactive oxygen species (ROSs, such as •O 2- , •OH, H2O2 and 1 O2), some of which are highly active in the degradation and mineralization of pollutants, and the process does not require additional consumption of other raw materials, only requires sunlight irradiation and the selection of suitable semiconductor materials as photocatalysts.

[0004] Graphitic carbon nitride (g-C3N4) is a typical photocatalyst with the advantages of low cost, good physical and chemical stability, high temperature resistance and corrosion resistance. It has broad application prospects in the degradation of organic pollutants, sterilization and disinfection. However, the unmodified g-C3N4 has a narrow visible light response range, poor photogenerated carrier transport capacity, and easy carrier recombination, which makes its photocatalytic reaction rate unsatisfactory, seriously limiting the development and application of g-C3N4. Therefore, it is urgent to improve the catalytic performance by modifying it to construct a composite photocatalyst to overcome the above shortcomings. Summary of the invention

[0005] In order to solve the deficiencies mentioned in the above-mentioned background technology, the purpose of the present invention is to provide a carbon nitride composite photocatalyst and its preparation method and application. The catalyst uses g-C3N4 as a light absorption active layer, and introduces phosphorus and potassium elements for co-doping, which regulates the electronic structure of the catalyst and changes the band edge position, thereby improving the generation ability of active oxygen intermediates and light absorption performance, and improving conductivity. At the same time, a co-catalyst CoS is introduced to form a special semiconductor heterojunction together with the original phosphorus and potassium co-doped catalyst. The heterojunction promotes the diffusion and transfer of photogenerated electrons, and improves the separation ability of photogenerated electrons and photogenerated holes, thereby extending the lifetime of photogenerated carriers.

[0006] The purpose of the present invention can be achieved by the following technical solutions: The invention provides a carbon nitride composite photocatalyst. The carbon nitride composite photocatalyst is phosphorus and potassium co-doped carbon nitride modified by cobalt sulfide. The carbon nitride composite photocatalyst has a particle stacking morphology, a particle size of 1-10 μm, an aspect ratio of 10:1-2:1, and a graphite phase. P, K, Co, and S elements are uniformly distributed in g-C3N4 particles. The doping ratio of each element in the carbon nitride composite photocatalyst is P 1.33-21.7%, K 3.94-41.2%, Co 0.412-8.27%, and S 0.216-4.57%.

[0007] Further preferably, the band gap of the composite photocatalyst is 2.50 eV ~ 2.98 eV.

[0008] A method for preparing a carbon nitride composite photocatalyst comprises the following steps: (1) Melamine and dipotassium hydrogen phosphate were added to deionized water. After ultrasonic dispersion, the entire solution was quickly transferred to a high-pressure reactor and heated to 180°C in a water bath for 24 hours. After the temperature of the reactor dropped to room temperature, the sample was washed with deionized water. After filtering, the sample was placed in a 60-85°C constant temperature drying oven for drying. The dried sample was then placed in a covered crucible, heated to 500-580°C, calcined for 2-6 hours, and cooled to room temperature to obtain a powder sample. (2) Take the powder sample obtained in step (1) and add it to a mixed solution containing cobalt nitrate and thiourea. After stirring for 1 hour, transfer the mixed solution to a high-pressure reactor and heat it in a water bath to 150° C. for 4 hours. After the temperature of the reactor drops to room temperature, wash the sample with deionized water and then dry it at 60~85° C. to obtain the carbon nitride composite photocatalyst.

[0009] Further preferably, in step (1), the mass ratio of melamine to dipotassium hydrogen phosphate is 1-5:0.05-0.5.

[0010] Further preferably, in step (2), the molar ratio of cobalt nitrate to thiourea is 1:2, and the molar concentration of cobalt nitrate in the mixed solution is 1-10 mM.

[0011] The invention discloses an application of a carbon nitride composite photocatalyst in the photocatalytic degradation of organic matter. The carbon nitride composite photocatalyst has excellent light absorption capacity and photocatalytic oxidation capacity, and promotes the photocatalytic degradation of organic pollutants.

[0012] Beneficial effects of the present invention: The carbon nitride composite photocatalyst of the present invention uses g-C3N4 as a light absorption active layer, and introduces phosphorus and potassium elements for co-doping, regulates the electronic structure of the catalyst, changes the band edge position, thereby improving the generation ability of active oxygen intermediates and light absorption performance, and improving conductivity; on this basis, the co-catalyst CoS is introduced to form a special semiconductor heterojunction together with the original phosphorus and potassium co-doped catalyst, and the heterojunction promotes the diffusion and transmission of photogenerated electrons, and improves the separation ability of photogenerated electrons and photogenerated holes, thereby prolonging the life of photogenerated carriers. In addition, the structure further regulates the electronic structure, expands the spectral response range and oxidation capacity. The composite catalyst is used for photocatalytic degradation of organic pollutants, and good results are achieved. Under the irradiation of simulated sunlight, its degradation effect on the organic pollutant RhB is not only better than conventional g-C3N4, phosphorus-doped g-C3N4 and potassium-doped g-C3N4, but also better than phosphorus and potassium co-doped g-C3N4 and CoS-modified g-C3N4. BRIEF DESCRIPTION OF THE DRAWINGS

[0013] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, for ordinary technicians in this field, other drawings can be obtained based on these drawings without paying any creative work.

[0014] Figure 1 XRD diagrams of g-C3N4 photocatalyst samples of Examples 1 to 3 and Comparative Examples 2 to 5; Figure 2 It is the SEM image of the g-C3N4 photocatalyst sample of Comparative Example 4 and Example 1; Figure 3 Element distribution diagram of g-C3N4 photocatalyst of Example 2 Figure 4 The optical absorption spectra and optical band gaps of the g-C3N4 samples of Example 3, Comparative Example 4 and Comparative Example 5; Figure 5 Optical photographs of g-C3N4 samples of Example 3, Comparative Example 4 and Comparative Example 5; Figure 6 This is a performance diagram of the photocatalytic degradation of RhB by g-C3N4 catalyst of Example 1 to Example 3 and Comparative Example 1 to Comparative Example 5. DETAILED DESCRIPTION

[0015] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0016] Example 1

[0017] A carbon nitride composite photocatalyst, wherein the carbon nitride composite photocatalyst is phosphorus and potassium co-doped carbon nitride modified with cobalt sulfide, the carbon nitride composite photocatalyst is in a particle stacking morphology, with a particle size of 1-10 μm, an aspect ratio of 10:1-2:1, the carbon nitride is a graphite phase, wherein P, K, Co, and S elements are uniformly distributed in the g-C3N4 particles; The method for preparing the carbon nitride composite photocatalyst comprises the following steps: (1) 2.5 g of melamine and 0.15 g of potassium dihydrogen phosphate were added to 35 mL of deionized water. After ultrasonic dispersion for 30 min, the entire solution was quickly transferred to a 50 mL high-pressure reactor for hydrothermal reaction at 180 °C for 24 h. After the reactor temperature dropped to room temperature, the sample was washed with deionized water and then dried at 80 °C for 12 h. The dried sample was placed in a crucible with a lid, heated to 550 °C, calcined for 4 h, and cooled to room temperature to obtain a powder sample. (2) Take 200 mg of the above powder sample and add it to 50 mL of a mixed solution containing cobalt nitrate and thiourea. The molar ratio of cobalt nitrate to thiourea is 1:2 and the molar concentration of cobalt nitrate is 3 mM. After stirring for 1 hour, the mixed solution is transferred to a 50 mL high-pressure reactor and placed in a drying oven and heated to 150°C. Hydrothermal treatment is performed for 4 hours. After the temperature of the reactor drops to room temperature, the sample is washed with deionized water and then dried at 80°C for 12 hours to obtain the final cobalt sulfide-modified phosphorus and potassium co-doped carbon nitride composite photocatalyst (CSKPCN-1).

[0018] Example 2

[0019] A carbon nitride composite photocatalyst, wherein the carbon nitride composite photocatalyst is phosphorus and potassium co-doped carbon nitride modified with cobalt sulfide, the carbon nitride composite photocatalyst is in a particle stacking morphology, with a particle size of 1-10 μm, an aspect ratio of 10:1-2:1, the carbon nitride is a graphite phase, wherein P, K, Co, and S elements are uniformly distributed in the g-C3N4 particles; The method for preparing the carbon nitride composite photocatalyst comprises the following steps: (1) 2.5 g of melamine and 0.18 g of potassium dihydrogen phosphate were added to 35 mL of deionized water. After ultrasonic dispersion for 30 min, the entire solution was quickly transferred to a 50 mL high-pressure reactor for hydrothermal reaction at 180 °C for 24 h. After the reactor temperature dropped to room temperature, the sample was washed with deionized water and then dried at 80 °C for 12 h. The dried sample was placed in a crucible with a lid, heated to 550 °C, calcined for 4 h, and cooled to room temperature to obtain a powder sample. (2) Take 200 mg of the above powder sample and add it to 50 mL of a mixed solution containing cobalt nitrate and thiourea. The molar ratio of cobalt nitrate to thiourea is 1:2 and the molar concentration of cobalt nitrate is 2 mM. After stirring for 1 hour, the mixed solution is transferred to a 50 mL high-pressure reactor and placed in a drying oven and heated to 150°C. Hydrothermal treatment is performed for 4 hours. After the temperature of the reactor drops to room temperature, the sample is washed with deionized water and then dried at 80°C for 12 hours to obtain the final cobalt sulfide-modified phosphorus and potassium co-doped carbon nitride composite photocatalyst (CSKPCN-2).

[0020] Example 3

[0021] A carbon nitride composite photocatalyst, wherein the carbon nitride composite photocatalyst is phosphorus and potassium co-doped carbon nitride modified with cobalt sulfide, the carbon nitride composite photocatalyst is in a particle stacking morphology, with a particle size of 1-10 μm, an aspect ratio of 10:1-2:1, the carbon nitride is a graphite phase, wherein P, K, Co, and S elements are uniformly distributed in the g-C3N4 particles; The method for preparing the carbon nitride composite photocatalyst comprises the following steps: (1) 2.5 g of melamine and 0.15 g of potassium dihydrogen phosphate were added to 35 mL of deionized water. After ultrasonic dispersion for 30 min, the entire solution was quickly transferred to a 50 mL high-pressure reactor for hydrothermal reaction at 180 °C for 24 h. After the reactor temperature dropped to room temperature, the sample was washed with deionized water and then dried at 80 °C for 12 h. The dried sample was placed in a crucible with a lid, heated to 550 °C, calcined for 4 h, and cooled to room temperature to obtain a powder sample. (2) Take 200 mg of the above powder sample and add it to 50 mL of a mixed solution containing cobalt nitrate and thiourea. The molar ratio of cobalt nitrate to thiourea is 1:2 and the molar concentration of cobalt nitrate is 6 mM. After stirring for 1 hour, the mixed solution is transferred to a 50 mL high-pressure reactor and placed in a drying oven and heated to 150°C. Hydrothermal treatment is performed for 4 hours. After the temperature of the reactor drops to room temperature, the sample is washed with deionized water and then dried at 80°C for 12 hours to obtain the final cobalt sulfide-modified phosphorus and potassium co-doped carbon nitride composite photocatalyst (CSKPCN-3).

[0022] Comparative Example 1 A method for preparing graphite carbon nitride (g-C3N4) comprises the following steps: adding 2.5 g of melamine to 35 mL of deionized water, and then ultrasonically dispersing the mixture for 30 min. The whole solution is then quickly transferred to a 50 mL high pressure reactor for a hydrothermal reaction at a temperature of 180°C for 24 h. When the temperature of the reactor drops to room temperature, the sample is washed with deionized water, and then dried at 80°C for 12 h. The dried sample is placed in a crucible with a lid, heated to 550°C, calcined for 4 h, and cooled to room temperature to obtain a powder sample, thereby obtaining a g-C3N4 sample.

[0023] Comparative Example 2 A preparation method of K-doped g-C3N4 comprises the following steps: adding 2.5 g of melamine and 0.064 g of potassium chloride into 35 mL of deionized water, and performing ultrasonic dispersion for 30 min. Then, the entire solution is rapidly transferred into a 50 mL high pressure reactor for a hydrothermal reaction at a temperature of 180° C. for 24 h. After the reactor temperature is lowered to room temperature, the sample is washed with deionized water, and then dried at 80° C. for 12 h. The dried sample is placed in a crucible with a lid, and the temperature is raised to 550° C., calcined for 4 h, and cooled to room temperature to obtain a powder sample, thereby obtaining K-doped g-C3N4 (KCN).

[0024] Comparative Example 3 A preparation method of P-doped g-C3N4 comprises the following steps: adding 2.5 g of melamine and 0.084 g of phosphoric acid into 35 mL of deionized water, and performing ultrasonic dispersion for 30 min. Then, the entire solution is rapidly transferred into a 50 mL high pressure reactor for a hydrothermal reaction at a temperature of 180° C. for 24 h. After the reactor temperature drops to room temperature, the sample is washed with deionized water, and then dried at 80° C. overnight. The dried sample is placed in a crucible with a lid, and the temperature is raised to 550° C., calcined for 4 h, and cooled to room temperature to obtain a powder sample, thereby obtaining P-doped g-C3N4 (PCN).

[0025] Comparative Example 4 A preparation method of K and P co-doped g-C3N4, comprising the following steps: adding 2.5 g of melamine and 0.15 g of potassium dihydrogen phosphate into 35 mL of deionized water, and performing ultrasonic dispersion for 30 min. Then, the entire solution is rapidly transferred into a 50 mL high pressure reactor for a hydrothermal reaction at a temperature of 180° C. for 24 h. After the reactor temperature is lowered to room temperature, the sample is washed with deionized water, and then dried at 80° C. for 12 h. The dried sample is placed in a crucible with a lid, heated to 550° C., calcined for 4 h, and cooled to room temperature to obtain a powder sample, thereby obtaining K and P co-doped g-C3N4 (KPCN).

[0026] Comparative Example 5 A method for preparing CoS-modified g-C3N4 comprises the following steps: (1) 2.5 g of melamine was added to 35 mL of deionized water. After ultrasonic dispersion for 30 min, the entire solution was quickly transferred to a 50 mL high-pressure reactor for hydrothermal reaction at 180 °C for 24 h. After the reactor temperature dropped to room temperature, the sample was washed with deionized water and then dried at 80 °C for 12 h. The dried sample was placed in a crucible with a lid, heated to 550 °C, calcined for 4 h, and cooled to room temperature to obtain a powder sample. (2) Take 200 mg of the above powder sample and add it to 50 mL of a mixed solution containing cobalt nitrate and thiourea. The molar ratio of cobalt nitrate to thiourea is 1:2 and the molar concentration of cobalt nitrate is 3 mM. After stirring for 1 hour, the mixed solution is transferred to a 50 mL high-pressure reactor and placed in a drying oven and heated to 150°C. Hydrothermal treatment is performed for 4 hours. After the temperature of the reactor drops to room temperature, the sample is washed with deionized water and then dried at 80°C for 12 hours to obtain CoS-modified g-C3N4 (CSCN).

[0027] Structural characterization The g-C3N4 photocatalyst samples obtained in Examples 1 to 3 and Comparative Examples 2 to 5 were analyzed by X-ray diffractometer (XRD). The test results are as follows: Figure 1 The results show that all catalyst samples of the embodiments and comparative examples have obvious characteristic diffraction peaks at 28.3°, retaining the basic phase of g-C3N4, and doping and loading of promoters do not change the phase.

[0028] The morphology of the g-C3N4 photocatalyst samples obtained in Comparative Example 4 and Example 1 was analyzed by scanning electron microscopy (SEM). Figure 2 The results show that the samples are all irregular particle accumulation morphology, composed of large particles (length greater than 10 microns, width greater than 1 micron) and a small amount of lamellae.

[0029] Energy dispersive X-ray spectroscopy (EDS) was used to analyze the element distribution of the g-C3N4 photocatalyst sample obtained in Example 2. The results are as follows: Figure 3 The results show that P, K, Co, and S elements are evenly distributed in g-C3N4 particles, proving that the cobalt sulfide-modified phosphorus and potassium co-doped carbon nitride composite photocatalyst was successfully synthesized.

[0030] The light absorption spectra of the g-C3N4 photocatalyst samples obtained in Example 3, Comparative Example 4 and Comparative Example 5 were measured using an ultraviolet-visible spectrophotometer (UV-vis). Figure 4 (a) The optical band gaps of the three samples were calculated based on the light absorption results. Figure 4(b) As shown. The results show that the band gap of the cobalt sulfide-modified phosphorus and potassium co-doped carbon nitride composite photocatalyst (CSKPCN-3) is only 2.87 eV, which is significantly smaller than the band gap of phosphorus and potassium co-doped carbon nitride (KPCN) (2.96 eV) and the band gap of cobalt sulfide-modified carbon nitride (CSCN) (2.91 eV), indicating that the light absorption capacity of CSKPCN has been significantly improved. The optical photos of the three samples are shown in Figure 5 As shown, it can be seen that with the increase of the band gap, the color of the sample gradually deepens, further proving that CSKPCN has the best light absorption ability.

[0031] The valence band position, conduction band position and band gap value of the catalyst materials of Examples 1 to 3 and Comparative Examples 1 to 5 were determined using X-ray valence band spectra and light absorption spectra, and the results are listed in Table 1. It can be seen that K and P co-doping regulates the band edge position, so that the catalyst has a stronger oxidation ability, which is conducive to the production of more active oxygen intermediates, thereby improving the degradation ability of organic pollutants. On this basis, after modifying CoS, the valence band top and the conduction band bottom positions are further moved down, and the band gap is further reduced, thereby improving the light absorption ability and photocatalytic oxidation ability, and promoting the photocatalytic degradation of organic pollutants. In addition, the results show that the synergistic effect of CoS modification and K and P co-doping is better than that of CoS modification alone and K and P doping alone.

[0032] Table 1 Physical and chemical performance parameters of materials in Examples 1 to 3 and Comparative Examples 1 to 5 Conduction band bottom (V) Valence band top (V) Bandgap (eV) Reaction rate constant () CN -0.79 2.19 2.98 0.00672 KCN -0.77 2.20 2.97 0.00674 PCN -0.73 2.22 2.95 0.01029 KPCN -0.71 2.25 2.96 0.01186 CSCN -0.59 2.32 2.91 0.01580 CSKPCN-1 -0.46 2.28 2.74 0.01670 CSKPCN-2 -0.54 2.26 2.80 0.01669 CSKPCN-3 -0.42 2.45 2.87 0.01635 Performance Testing The photocatalytic degradation of RhB was carried out by photodegrading a Rhodamine B (RhB) solution to evaluate the photocatalytic activity of the catalyst. In the photocatalytic degradation of RhB experiment, 10 mg of each of the g-C3N4 samples of Examples 1 to 3 and Comparative Examples 1 to 5 were weighed and ultrasonically dispersed in 50 mL of a 10 mg L -1 The uniformly dispersed solution was then placed in a double-layer quartz reaction vessel. The dispersion was placed in the dark and stirred continuously for 30 min to reach adsorption / desorption equilibrium, and then illuminated for degradation testing. The light source used during the illumination process was a 300 W xenon lamp with a light intensity of 100 mW cm -2 During the irradiation process, 3.5 mL of the dispersion was taken from the reaction vessel every 20 min, centrifuged for 3 min, and the supernatant was placed in a cuvette. The absorbance was measured using a UV-visible spectrophotometer, and the photodegradation rate of the catalyst was calculated according to formula (1).

[0033] (1) In the formula, and are the concentration of RhB before illumination and the light absorption value of RhB solution at 535 nm, respectively. C and A are the concentration of RhB and the absorption value at 535 nm after different illumination time, respectively. The curve of the measured photodegradation rate changing with illumination time is shown in Figure 6 As shown, it can be seen that the phosphorus and potassium co-doped carbon nitride composite photocatalyst modified by cobalt sulfide has the best degradation ability for the organic pollutant RhB.

[0034] The reaction kinetics of photodegradation of RhB by g-C3N4 sample can be simulated as a first-order kinetic model, as shown in Eq. (2).

[0035] (2) Wherein, is the initial concentration of RhB without illumination, C is the concentration of RhB solution after illumination for a certain period of time, k is the reaction rate constant, and t is the reaction time. The k values ​​of different catalyst samples are listed in Table 1. It can be seen that the phosphorus and potassium co-doped carbon nitride composite photocatalyst modified by cobalt sulfide has the largest reaction rate constant, indicating that the phosphorus and potassium co-doped carbon nitride composite photocatalyst modified by cobalt sulfide has the strongest photocatalytic degradation ability for RhB.

[0036] It can be seen from the above experimental results that the cobalt sulfide modified phosphorus and potassium co-doped carbon nitride composite photocatalyst described in the present invention has excellent photocatalytic degradation ability of organic pollutants. The degradation effect of the organic pollutant RhB is not only better than that of conventional g-C3N4, phosphorus-doped g-C3N4 and potassium-doped g-C3N4, but also better than that of phosphorus and potassium co-doped g-C3N4 and CoS-modified g-C3N4. This shows that the catalyst prepared by this method utilizes the synergistic effect of each component to improve the original defects and problems of the g-C3N4 catalyst and has good photocatalytic activity.

[0037] In the description of this specification, the description with reference to the terms "one embodiment", "example", "specific example", etc. means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representation of the above terms does not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described can be combined in any one or more embodiments or examples in a suitable manner.

[0038] The above shows and describes the basic principles, main features and advantages of the present invention. Those skilled in the art should understand that the present invention is not limited to the above embodiments, and the above embodiments and descriptions are only for explaining the principles of the present invention. Without departing from the spirit and scope of the present invention, the present invention may have various changes and improvements, and these changes and improvements all fall within the scope of the present invention to be protected.

Claims

1. A carbon nitride composite photocatalyst, characterized in that: The carbon nitride composite photocatalyst is phosphorus and potassium co-doped carbon nitride modified by cobalt sulfide. The carbon nitride composite photocatalyst has a particle stacking morphology, a particle size of 1-10 μm, an aspect ratio of 10:1-2:1, and a graphite phase. P, K, Co, and S elements are uniformly distributed in g-C3N4 particles. The doping ratio of each element in the carbon nitride composite photocatalyst is P 1.33-21.7%, K 3.94-41.2%, Co 0.412-8.27%, and S 0.216-4.57%.

2. The carbon nitride composite photocatalyst according to claim 1, characterized in that: The band gap of the composite photocatalyst is 2.50 eV ~ 2.98 eV.

3. The method for preparing the carbon nitride composite photocatalyst according to any one of claims 1 to 2, characterized in that: The following steps are involved: (1) Melamine and dipotassium hydrogen phosphate were added to deionized water. After ultrasonic dispersion, the entire solution was quickly transferred to a high-pressure reactor and heated to 180°C in a water bath for 24 hours. After the temperature of the reactor dropped to room temperature, the sample was washed with deionized water. After filtering, the sample was placed in a 60-85°C constant temperature drying oven for drying. The dried sample was then placed in a covered crucible, heated to 500-580°C, calcined for 2-6 hours, and cooled to room temperature to obtain a powder sample. (2) Take the powder sample obtained in step (1) and add it to a mixed solution containing cobalt nitrate and thiourea. After stirring for 1 hour, transfer the mixed solution to a high-pressure reactor and heat it to 150°C in a water bath for 4 hours. After the temperature of the reactor drops to room temperature, wash the sample with deionized water and then dry it at 60~85°C to obtain the carbon nitride composite photocatalyst.

4. The method for preparing the carbon nitride composite photocatalyst according to claim 3, characterized in that: In the step (1), the mass ratio of melamine to dipotassium hydrogen phosphate is 1-5:0.05-0.

5.

5. The method for preparing the carbon nitride composite photocatalyst according to claim 3, characterized in that: In the step (2), the molar ratio of cobalt nitrate to thiourea is 1:2, and the molar concentration of cobalt nitrate in the mixed solution is 1-10 mM.

6. Use of the carbon nitride composite photocatalyst according to any one of claims 1 to 2 in photocatalytic degradation of organic matter, characterized in that: The carbon nitride composite photocatalyst has excellent light absorption ability and photocatalytic oxidation ability, and promotes the photocatalytic degradation of organic pollutants.